2022
DOI: 10.3389/fonc.2022.1035487
|View full text |Cite
|
Sign up to set email alerts
|

The role of lncRNAs in regulation of DKD and diabetes-related cancer

Abstract: Diabetes mellitus often results in several complications, such as diabetic kidney disease (DKD) and end-stage renal diseases (ESRDs). Cancer patients often have the dysregulated glucose metabolism. Abnormal glucose metabolism can enhance the tumor malignant progression. Recently, lncRNAs have been reported to regulate the key proteins and signaling pathways in DKD development and progression and in cancer patients with diabetes. In this review article, we elaborate the evidence to support the function of lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 132 publications
0
1
0
Order By: Relevance
“…It has been shown that miRNA can bind to specific mRNA molecules and cause the inhibition of translation or degradation, leading to regulation of gene expression. LncRNAs with longer than 200 nucleotides have been identified to involve in diverse diseases via regulating gene expression and chromatin remodeling, including cancer, neurodegenerative diseases and cardiovascular disorders ( Jiang et al, 2020 ; Cheng et al, 2022 ; Gareev et al, 2022 ; Sufianova et al, 2022 ; Xie et al, 2022 ). LncRNAs have gained significant attention and play crucial regulatory roles in osteoarthritis ( Chen et al, 2017 ; Abbasifard et al, 2020 ; Tu et al, 2020 ; Wang et al, 2022 ; Okuyan and Begen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that miRNA can bind to specific mRNA molecules and cause the inhibition of translation or degradation, leading to regulation of gene expression. LncRNAs with longer than 200 nucleotides have been identified to involve in diverse diseases via regulating gene expression and chromatin remodeling, including cancer, neurodegenerative diseases and cardiovascular disorders ( Jiang et al, 2020 ; Cheng et al, 2022 ; Gareev et al, 2022 ; Sufianova et al, 2022 ; Xie et al, 2022 ). LncRNAs have gained significant attention and play crucial regulatory roles in osteoarthritis ( Chen et al, 2017 ; Abbasifard et al, 2020 ; Tu et al, 2020 ; Wang et al, 2022 ; Okuyan and Begen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%